NU: Pergumulan Islam dan ABRI di Masa Kontemporer - J.H. Meuleman (Studia Islamika, 1997)
The following article offers a review of a recent book bu Andree Feillard, followed by an extensive summary. This abstract will present the main points of the review.During the long period she lived in Indonesia, the attention of the French researcher and journalist, Andree Feillard, was particularly attracted to the large Indonesian traditionalist Muslim movement, the Nahdatul Ulama (NU). This is the main object of the book under review, whose title in English translation is "Islam anad Army in Contemporary Indonesia. The Pioneers of Tradition". The main objective of the book is to explain why in 1984 the NU decided to return to its original policy of concentrating on educational and social activities, after a long period of involvement in parliamentary politics. A futher aim of the book is to analyze the impact of this decision.DOI: 10.15408/sdi.v4i1.791